Women’s satisfaction with their urban health extension programme and associated factors in Gondar administrative city, northwest Ethiopia: a community-based cross-sectional study - Sisay Molla; Amsalu Feleke; Chalie Tadie Tsehay (BMJ Open)
Objectives Ethiopia is a developing country striving to achieve universal health coverage using the health extension programme. There is limited evidence about Ethiopian women’s satisfaction with their urban health extension programme. Thus, this study was aimed at assessing the level of women’s satisfaction with their urban health extension services and associated factors in Gondar administrative city of northwest Ethiopia and elucidate factors associated with its access and use.Design Cross-sectional study.Setting Community.Participants Randomly selected 744 women were interviewed using a structured interviewer-administered questionnaire.Outcome Satisfaction of women over 17 years of age with their urban health extension programme (use and services).Results Some 29.4% (95% CI 26.2 to 32.5) of women were satisfied with their urban health extension programme. Divorced women (adjusted OR (AOR): 0.35, 95% CI 0.14 to 0.85), women in the age group of 45–53 years (AOR: 0.35, 95% CI 0.14 to 0.85), private employees (AOR: 0.35, 95% CI 0.14 to 0.85), unsatisfactory knowledge (AOR: 0.13, 95% CI 0.07 to 0.25) and perceived accessibility of health extension workers (AOR: 0.99, 95% CI 0.06 to 0.17) were factors associated with women’s satisfaction with their urban health extension programme.Conclusions Women’s satisfaction with their urban health extension programme was low. This finding was associated with age, marital status, occupation, knowledge of participants and women’s perceived accessibility of services. Therefore, increasing awareness about the programme, promoting and improving accessibility of services, particularly by mothers, may augment the utilisation of the programme ultimately leads to efficient use of scarce healthcare resources in Ethiopia.